Pengaruh Kecerdasan Naturalis Terhadap Pro Environmental Behavior - Kamila Nur Afifah; I Made Putrawan; Diana Vivanti (IJEEM - Indonesian Journal of Environmental Education and Management, 2021)
Environmental problems have occurred in various regions. This problem is a problem that must be solved by many parties, including students. Pro Environmental Behavior is needed by someone to improve environmental quality. Naturalistic intelligence is one of the factors affecting Pro Environmental Behavior. This study aims to determine the naturalistic intelligence factor towards the pro environmental behavior. This study involved 48 students in Jakarta as randomly selected samples. There are two instruments that had been developed to measure these variables. Each of these instruments has a reliability of 0.852 and 0.376. Data has been analyzed by T test. The results showed that there was a difference in the average score of the pro-environmental behavior of students who had high and low naturalistic intelligence at É‘ = 0.3 (1.1). These results mean that there is an effect of naturalistic intelligence on the pro environmental behavior. Therefore, in increasing the pro-environmental behavior of students, factors such as naturalist intelligence can be considered.